PENANGANAN MASALAH PERSAMPAHAN DAN LIMBAH CAIR DI PROPINSI BANTEN - Fitria Riany Eris (Jurnal Agroekoteknologi, 2009)
ABSTRACTSolid and liquid waste are important environmental problems that if not managed well, it great potential to reduce the quality of the environment and health. Efforts to overcome the solid and liquid waste requires an approach. The objective of this research is to know the handling of environmental issues, especially solid and liquid waste handlers in Banten Province and provides an alternative waste management in overcoming it. Research done by taking a secondary data from various institutions related to research such as this BAPEDAL Province Banten, the BPS Banten Province and library literature. Handling environmental issues in Banten Province is stressed to technology and financial approach rather than through a social approach, partnership, cultural, political, legal and institutional arrangements. In connection with this effort will need, a new approach and change the paradigm in the management of solid and liquid waste. For example, the management of solid waste is concentrated to handle waste only and it should be changed to penyadaran process community and in the case of waste management.Key words: Solid Waste, Liquid Waste